Electronic structure and magnetic anisotropy design of functional metal complexes - Raza, Arsen; Perfetti, Mauro (Coordination chemistry reviews, 2023)
[Display omitted] •Two chemically controllable parameters can assess the potential use of a magnetic material.•Coordination chemistry can be used to engineer functional magnetic materials.•Five types of magnetic functional materials are analysed.•The compatibility between different functionalities is discussed. Chemical guidelines to target a well-defined electronic structure and magnetic anisotropy are of primary importance in physics, chemistry and biology. Our literature overview highlights that engineering the energy gap between the ground and first excited state and tailoring the magnetic anisotropy of paramagnetic molecules is an excellent starting point for boosting the performances of many molecular materials with emerging properties of technological relevance such as Single Molecule Magnets, Pseudo Contact Shift agents, Optically Addressable Qubits, Magnetic Refrigerants, and Magnetic Anisotropy Switches. We also discuss the compatibility between different functionalities.